Democracy and principles of socio-economic development - A. A. Sychev; E. V. Zaytseva; P. S. Tolkachev (Вестник университета)
The article examines the existing political and economic trends: democratic and authoritarian forms of government. An attempt is made to describe the essential content of the values of democracy, as well as their implementation in the economic sphere. All this justifies the role of e-technologies only as a quantitative factor in the development of democracy. It is shown that the form of government is primarily based on personal value choice, which leads to effective or ineffective socio-political equilibrium states. It is shown that the construction of supporting democratic institutions does not implement the principles of power: service and hierarchy. Therefore, the transition to a new qualitative state is possible through education, awareness of the principles of power, their free acceptance, but cannot be carried out artificially, through a system of institutions introduced from the outside.